The chronicles of Fernão Lopes. - Lopes, Fernão, approximately 1380- (Textos B, 2023)
Volume IV of the first complete English translation of the chronicles of Fernão Lopes chronicles the Battle of Aljubarrota (1385), which secured the throne for João I, his marriage to Philippa of Lancaster, and his reign up to 1411.